IMPLEMENTASI PENDEKATAN SAVI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN AKUNTANSI - Nia Islamawati, (Pendidikan Ekonomi, 2011)
The study is aimed to find out the teachers activities of instructional management, the students activities in learning process, and the students response to the use of SAVI approach incorporated with the Numbered Head Together of cooperative learning model.The study was classroom action research, consisting of three cycles. The subjects of the study were the eleventh graders of AK I SMKN I Sooko Mojokerto. The data were then analyzed descriptively. The result shows that both the teachers and students activities indicated gradual increases the three cycles. The students learning outcomes  also went up in each cycle. Additionally, the students showed positive responses to the use of SAVI through NHT type of cooperative learning model.